1993
DOI: 10.1128/aac.37.9.2009
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of biapenem against clinical isolates of gram-positive and gram-negative bacteria

Abstract: The in vitro activity of biapenem, a new carbapenem previously designated L-627, was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 7 publications
1
15
0
2
Order By: Relevance
“…Biapenem has a broad spectrum of in vitro antibacterial activity against gram-negative (including blactamase-producing strains and P. aeruginosa ), grampositive, and anaerobic bacteria (10,11). A previous study demonstrated that biapenem is as effective and well tolerated as imipenem/cilastatin in the treatment of intermediate and severe bacterial infections (11).…”
Section: Discussionmentioning
confidence: 99%
“…Biapenem has a broad spectrum of in vitro antibacterial activity against gram-negative (including blactamase-producing strains and P. aeruginosa ), grampositive, and anaerobic bacteria (10,11). A previous study demonstrated that biapenem is as effective and well tolerated as imipenem/cilastatin in the treatment of intermediate and severe bacterial infections (11).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent observations have prompted us to investigate in detail the kinetics of interaction between the novel carbapenem antibiotic biapenem (8,27,41) and active-site serine and metallo-␤-lactamases. These observations include the discovery of a plasmid-mediated metallo-␤-lactamase in P. aeruginosa (40); the emergence of strains of Bacteroides spp.…”
mentioning
confidence: 99%
“…In both instances, resistance to ␤-lactams can be attributed to the presence of penicillin-binding proteins with reduced affinities for these agents (7,8,14,16,22). Neither of the two more recently developed carbapenems, meropenem and biapenem, offers any activity advantage over imipenem against these organisms in particular or against gram-positive bacteria in general (13,20).…”
mentioning
confidence: 99%
“…Strains of streptococci demonstrating resistance to ␤-lactams and strains of vancomycinresistant enterococci had been referred to our collection from a variety of sources (13,20). L-695,256 and imipenem were provided by Merck, Sharp & Dohme Research Laboratories, Rahway, N.J. Other susceptibility reference powders were gifts from the indicated sources: oxacillin, Bristol-Myers Squibb Co., Syracuse, N.Y.; clindamycin, Upjohn Co., Kalamazoo, Mich.; erythromycin and vancomycin, Eli Lilly & Co., Indianapolis, Ind.…”
mentioning
confidence: 99%
See 1 more Smart Citation